The Lourinhã Formation - Mateus, O. (2017)
We thank Vasco Ribeiro for the many discussions about the regional geology, and perusing the manuscript, to Simão Mateus and Nuno Farinha for the illustrations, and to João Pais and Rogério Rocha for the reviewing and editing. This work is a contribution to projects funded by the “Fundação para a Ciência e a Tecnologia” (FCT) and COMPETE Program/FEDER European Fund, which we thank.